An Analysis Upon Competency-Based Education and Training: the Concept and Implications: Exploring the Potential of Competency-Based Education (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Competency-based education could be an exciting and valuable concept.However, in order to be so, educators, policy makers, and the public will haveto be willing to entertain some substantial departures from traditionaleducational assumptions and practices. The following offers a broader view ofthis concept and some of its important implications for school systems.